Comparative Evaluation of Non-Steroidal Anti-Inflammatory Drugs on Ovarian Microstructural Anatomy, Serum Antioxidants and Hormones in Wistar Rats - Kia, Balakumo E; Edagha, Innocent A; Umoh, Idorenyin U; Edagha, Edelungudi I; Bassey, Eno-Obong I; Peter, Alice J; Ataben, Moses A (Journal of Health Science and Medical Research, 2025)
Objective: Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used for the management of dysmenorrhea. Additionally, self-medication involving combinations of NSAIDs is frequent. We hypothesized that exposure to NSAIDs, either singly or concomitantly, may alter ovarian microstructures, hormones, and antioxidative status. Material and Methods: Forty young, adult female Wistar rats, weighing between 122-173 g, were divided into eight groups (A-H): five rats per group. Group A served as the control and received distilled water (5 mL/kg body weight). Group B received piroxicam (0.3 mg/kg), Group C received Ibuprofen (6.7 mg/kg), and Group D received diclofenac (1.7 mg/kg). Groups E, F, and G were administered combinations of two NSAIDs: piroxicam+ibuprofen (0.3 mg/kg+6.7 mg/kg), piroxicam+diclofenac (0.3 mg/kg+1.7 mg/kg), and ibuprofen+diclofenac (6.7 mg/kg+1.7 mg/kg), respectively. Group H received a combination of all three NSAIDs: piroxicam, ibuprofen, and diclofenac (0.3 mg/kg+6.7 mg/kg+1.7 mg/kg). All administrations lasted for 3 days, and animals were sacrificed 24 hours later under ketamine anesthesia. Blood and ovaries were harvested for analyses using standard protocols. Results: Ovarian histology demonstrated stromal hyperplasia, degenerative zona-pellucida, atretic and vacuolated follicles in groups D to H. Progesterone and estradiol concentrations showed increasing trends in groups C, D, F, G, and H compared to A. Superoxide dismutase concentrations significantly (p-value<0.05) increased in drug-administered groups, except in B and H, compared to the normal control (NC). All groups had significantly (p-value<0.05) increased catalase and glutathione peroxidase concentrations compared to the NC group, except group B. Conclusion: A 3-day NSAIDs oral administration is associated with gonadotoxicities in the ascending order: diclofenac >ibuprofen >piroxicam, and in the combination groups: piroxicam+ibuprofen+diclofenac >piroxicam+diclofenac; ibuprofen+diclofenac; piroxicam+ibuprofen, respectively, in female Wistar rats.